The Relationship of Student Readiness with Mathematics Learning Outcome at Package C Program in SKB Agam District - Riyan Prasetiyo; Wirdatul' Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The background of this research is the low learning outcomes of the learning community in the mathematics lesson Package C learning program at the SKB of Agam Regency. This situation is allegedly due to the low learning readiness of the learning residents. This study aims to: 1) look at the description of the readiness of the learning citizens in the mathematics subject in Package C SKB Agam, 2) see the description of the learning outcomes obtained by the citizens learning Package C SKB Agam, 3) see the relationship between the readiness of learning residents and learning outcomes mathematics subject in the SKB Agam package C program.This research was conducted using a correlational type quantitative approach which aims to examine the relationship between the readiness of learning citizens and learning outcomes. The research population included all Package C learning residents at SKB Agam which consisted of 30 learning residents. The sampling technique was Random Sampling and 20 people were taken. The data collection method uses angles with a statement list format as a tool in collecting data, techniques in analyzing data use the proportion formula and to look for correlations use the Rank Order formula.The results of the study prove that: 1) The readiness of the residents to study in the package C program at the Agam Skb is classified as low; 2) The results of studying mathematics in the package C program at SKB Agam show that 12 students have scores between 70-74 with the highest proportion of 60%, and; 3) there is a significant relationship between the readiness of learning residents and learning outcomes in mathematics in the package c program at the SKB AgamKeywords: Readiness to Learn; Learning outcomes